Analysis of Volatile Flavor Components in Three Onion by Headspace Solid Phase Microextraction Combined with Gas Chromatography-Mass Spectrometry - Rong WANG; Wenjin ZENG; Pan LIU; Li ZHOU; Xingquan REN; Xuefen YANG; Jun ZHAO (Shipin gongye ke-ji, 2022)
In order to study the volatile composition of onion, the volatile flavoring substances of the onion were extracted by headspace solid phase microextraction and determined by gas chromatography-mass spectrometry. The effects of extraction fiber head, extraction temperature, extraction time and desorption time on the total peak area and the number of effective compounds were investigated. The optimum extraction conditions were determined as follows: Extraction fiber 50/30 μm DVB/CAR/PDMS, extraction temperature 60 ℃, extraction time 60 min and desorption time 5 min. Under the optimum experimental conditions, the volatile compounds of onion with three different colors were analyzed and identified. The results showed that a total of 61 kinds of volatile flavor compounds were identified. A total of 37, 40 and 49 volatile flavor compounds were detected in the white, red, and yellow onions, respectively, and the peak area content of these volatile flavor compounds accounted for 70.29%, 81.92% and 79.03% of the total volatile components, respectively. In the 61 volatile flavor compounds, 27 were sulfur compounds, 13 were aldehydes, 13 were alcohols, 4 were ketones and 4 were others. There were 22 kinds of volatile components in the three color onions, of which sulfur-containing compounds account for a relatively large proportion, especially the relative content of diisopropyl disulfide and (E)-1-propenyl-2-propenyl disulfide. The sum of the volatile components of the three color onions accounted for more than 20%, which contributed a lot to the formation of the characteristic flavor of onions. The relative content of sulfur compounds in red and yellow onions was much higher than that of white onions. The relative content of 2-methyl-2-pentenoaldehyde in red onions was higher than that of white and yellow onions.